Implementasi Wisata Syariah Lombok dalam Perspektif Maqashid Syariah - Mulyono Jamal; Hamid Fahmi Zarkasyi; Haerul Akmal; Tesa Mellina (AL-ISTINBATH : Jurnal Hukum Islam, 2019)
Sharia tourism is one of the tourism concepts applied based on sharia principles. In recent years, Islamic tourism has mushroomed in several regions in Indonesia and even in the world, with different concepts. This concept is not only a media for the promotion of the regions that want to apply it, but more than that the tourism carried out by a person can strengthen his creed and belief, if carried out in accordance with Islamic principles. However, how is the application of sharia tourism in accordance with sharia principles? The concept of Islamic tourism which should be applied?, There are still many unknowns. So it takes an in-depth understanding of the concept of sharia tourism, and the need for a research related to this. Researchers see a relationship between maqoshid sharia with sharia tourism currently being applied. This study aims to determine the application of Islamic tourism in the perspective of Islamic maqoshid, with Lombok as the object of study. This type of research is qualitative research. Data collection method is done by interview and observation. Interviews were conducted on 10 respondents and took 5 tourism objects that became tourist icons in 5 districts in Lombok as research samples. The results of this study indicate that there is a relationship between maqoshid sharia in the application of sharia tourism, namely in the safeguarding of religion, soul, reason, descent and wealth. So the applied sharia tourism must include five safeguards in sharia maqoshid. While the application of Lombok sharia tourism in the maqoshid sharia perspective has not yet reached the five aspects of safeguards.